Empowering the urban youth fostering health, well-being, and resilience through the design of a post-pandemic Youth Wellness and Recreation Center - Mamangun-Roque, Ruby Ann; Gozon, Patrick Andrew E. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
Social isolation and fear due to the COVID-19 pandemic caused deterioration in youth physical and mental health. The worsening natural disasters brought about by climate change have left the youth even more vulnerable. This research aims to address youth health, well-being, and resilience in susceptible urban areas such as Navotas City by exploring immersive wellness and recreation through biophilic design while considering natural and biological (pandemic) disaster resilience. In the conduct of the study, initial research through literature review, precedent studies, and site analysis was performed to understand the relevant biophilic, and disaster-resilient design strategies and the emerging parameters for the new normal. Key expert informants were interviewed regarding improvement strategies for providing activities and amenities that promote wellness, biophilic design, as well as disaster-resilient design. Youth informants were surveyed to inquire about their preferences and desires for the facility and determine user-sensitive solutions. All the information was sorted and analyzed to set the design parameters. User behavior analysis and spatial analysis were performed for zoning, space programming, and then the conceptualization of the design. Following the integrated framework based on the World GBC framework for health and well-being and UNICEF-RET youth resilience approach, the final design was able to: offer avenues for carrying out positive experiences that cultivate health and wellness, such as physical activities, sports, and fun recreational activities; encourage meaningful relationships through opportunities for social interaction; include facilities for learning health and disaster risk reduction and climate change action; and provide a holistic, restorative environment by offering immersive wellness through biophilic strategies, designing a resilient building that overcomes natural disasters, and considering the parameters for the new normal – to empower the urban youth for the present and future times.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Recreation centers -- Navotas City; Urban youth -- Navotas City; Youth wellness -- Navotas City